Combined Permethrin and Salt Water Immersion Effects on Eosinophils, Immunoglobulin E, Histamine, and C3 Complement in Scabies Patients - Reqgi First Trasia; Endang Purwaningsih; Tjandra Yoga Aditama; Sri Wahyu Herlinawati (Althea Medical Journal, 2026)
Background: Scabies reduces quality of life due to intense nocturnal pruritus. Pruritus is associated with hypereosinophilia, increased immunoglobulin E (IgE), histamine release, and complement C3 activation. This study aimed to determine the effectiveness of combined permethrin and salt-water immersion therapy in reducing eosinophil counts, IgE, histamine, and complement C3 levels in patients with scabies.Methods: A quasi-experimental pre-test–post-test control group study was conducted among 92 students with scabies at an Islamic boarding school in Banten Province, Indonesia, from December 2024 to December 2025. Participants were selected using purposive sampling and divided into intervention and control groups. The intervention group received combined permethrin and warm salt-water immersion therapy, while the control group received permethrin alone. Eosinophil count, IgE, histamine, and complement C3 levels were measured before and after treatment. Data were analyzed using paired and independent t-tests.Results: Significant reductions were observed in the intervention group after therapy in eosinophils (t=65.0; p<0.001), IgE (t=152.9; p<0.001), histamine (t=152.1; p<0.001), and complement C3 (t=152.4; p<0.001). Post-treatment comparisons showed significant differences between groups for eosinophils (t=2.07; p<0.05), IgE (t=2.66; p<0.05), histamine (t=2.09; p<0.05), and complement C3 (t=4.25; p<0.001).Conclusions: Combined permethrin and warm salt-water immersion therapy significantly reduced inflammatory and immunological markers in patients with scabies and may help alleviate nocturnal pruritus.